The witch's boy - Barnhill, Kelly Regan (Algonquin Young Readers, 2015)
When a Bandit King comes to take the magic that Ned's mother, a witch, is meant to protect, the stuttering, weak boy villagers think should have drowned rather than his twin protects his family and community. Meanwhile, in the woods, the Bandit's daughter puzzles over a mystery that ties her to Ned. The two must find a way to trust each other if they want to stop the oncoming war between their two kingdoms.